Presence and resistance of Streptococcus agalactiae in vaginal specimens of pregnant and adult non-pregnant women and association with other aerobic bacteria - Fatima Numanović; Jasmina Smajlović; Merima Gegić; Zineta Delibegović; Sabaheta Bektaš; Jasmina Nurkić; Emir Halilović (Medicinski glasnik, 2017)
Aim: To determine the prevalence rate and resistance profile of Streptococcus agalactiae (S. agalactiae) in vaginal swabs of pregnant and adult non-pregnant women in the Tuzla region, Bosnia and Herzegovina (B&H), as well as its association with other aerobic bacteria. Methods: This prospective study included 200 women, 100 pregnant and 100 adult non-pregnant. The research was conducted at the Institute of Microbiology, University Clinical Center Tuzla from October to December 2015. Standard aerobic microbiological techniques were used for isolation and identification of S. agalactiae and other aerobic bacteria. Antimicrobial susceptibility was determined by the disk diffusion and microdilution method (VITEK 2/AES instrument). Results: Among 200 vaginal swabs, 17 (8.50%) were positive for S. agalactiae, e. g., 7% (7/100) of pregnant and 10% (10/100) of adult non-pregnant women. In the pregnant group, 71.4% (5/7) of S. agalactiae isolates were susceptible to clindamycin and 85.7% (6/7) to erythromycin. In the adult non-pregnant group, only resistance to clindamycin was observed in one patient (1/10; 10%). S. agalactiae as single pathogen was isolated in 57.14% (4/7) of pregnant and 60% (6/10) of adult non-pregnant S. agalactiae positive women. In mixed microbial cultures S. agalactiae was most frequently associated with Enterococcus faecalis and Escherichia coli. Conclusion: The rate of S. agalactiae positive women in the population of pregnant and adult non-pregnant women of Tuzla Canton, B&H is comparable with other European countries. Large studies are needed to develop a common national strategy for the prevention of S. agalactiae infection in B&H, especially during pregnancy.
Keywords: vaginal diseases; reproductive tract infections; bacterial infections